STUDENT'S LANGUAGE LEARNING STRATGIES IN LISTENING - Ariani, Retno; Arifin, Zainal; Riyanti, Dwi (Journal of English Education Program, 2020)
This research was aimed to describe language learning strategies in listening used by a third semester student of English Education Study Program who gets high achievement in listening English comprehension. This research was a qualitative research. The subject of this research was a successful language learner from a third semester student. This research was a case study which used observation and interview as the instruments of data collecting. The observation was done using direct and indirect observation and for the interview was done using semi structured interview that supported by a narrative analysis. The result of data analysis indicated that the student who categorized as a successful language learner in listening comprehension used the four framework of  listening strategies  by Goh and Kaur (2017) as the representative of language learning strategies in listening which proposed by O’Malley and Chamot (1990). Based on the result, the student who gets high achievement in listening English comprehension employed four strategies namely directed/selective attention strategies, planning and evaluation strategies, problem solving strategies and mental translation strategies. The findings revealed that the student who categorized as a successful language learner in this research was not achieving the goal of learning instantly